2013
DOI: 10.1016/j.neuron.2013.03.026
|View full text |Cite|
|
Sign up to set email alerts
|

CGG Repeat-Associated Translation Mediates Neurodegeneration in Fragile X Tremor Ataxia Syndrome

Abstract: Fragile X-associated Tremor Ataxia Syndrome (FXTAS) results from a CGG repeat expansion in the 5’UTR of FMR1. This repeat is thought to elicit toxicity as RNA yet disease brains contain ubiquitin-positive neuronal inclusions, a pathologic hallmark of protein-mediated neurodegeneration. We explain this paradox by demonstrating that CGG repeats trigger repeat associated non-AUG initiated (RAN) translation of a cryptic polyglycine-containing protein, FMRpolyG. FMRpolyG accumulates in ubiquitin-positive inclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
673
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 426 publications
(705 citation statements)
references
References 49 publications
30
673
1
1
Order By: Relevance
“…We need to recognise that the threshold of being a pathogenic repeat is much lower than was previously being thought. It is also possible that the mechanism underlying SCA36 is similar to the RAN translation mechanism proposed in DM1, SCA828 and recently confirmed in C9orf72 29 30-associated FTD/ALS and FXTAS 31…”
Section: Discussionmentioning
confidence: 64%
“…We need to recognise that the threshold of being a pathogenic repeat is much lower than was previously being thought. It is also possible that the mechanism underlying SCA36 is similar to the RAN translation mechanism proposed in DM1, SCA828 and recently confirmed in C9orf72 29 30-associated FTD/ALS and FXTAS 31…”
Section: Discussionmentioning
confidence: 64%
“…(67). However, it remains to be determined whether RAN products contribute to the neurological phenotype in FXTAS.…”
Section: Discussionmentioning
confidence: 99%
“…The C(C)UG exp foci in DM and the rGGGGCC exp in C9ORF72 ALS/FTD appear more compact, likely due to tighter interactions between the RNA and bound proteins, while rCGG exp -containing inclusions in FXTAS are larger and more diffuse structures that contain many proteins, including lamins and MBNL1 (Hagerman, 2013). FXTAS brains also contain ubiquitin-positive neuronal protein inclusions that contain polyglycine (FMRpolyG) generated by RAN translation (Todd et al, 2013). An important question to address in future studies will be whether the structural distinctions between RNA foci and inclusions reflect fundamental differences in the pathogenic pathway.…”
Section: Overview Of Rna Gain-of-function Disease Mechanismsmentioning
confidence: 99%
“…It has been reported that some aspects of the disease, like cognitive/behavioral dysfunction, are due to a decrease in FMRP levels in the amygdala (Hessl et al, 2011). Similar to DM and SCA8, CGG exp RNA undergoes RAN translation producing polyglycine in patient tissues and rCGG exp -induced toxicity is seen in cell and animal repeat expressing models (Todd et al, 2013). The transcription of long non-coding (lnc) RNAs and the occurrence of antisense transcription at the FMR1 locus, as well as RAN translation of those transcripts, further widens the repertoire of processes associated with neurotoxicity (Ladd et al, 2007; Pastori et al, 2014).…”
Section: Fragile X and Fragile X-associated Tremor/ataxia Syndromementioning
confidence: 99%